PENGARUH PENERAPAN GAME JEOPARDY DALAM PEMBELAJARAN REMEDIAL TERHADAP AKTIVITAS DAN HASIL BELAJAR MATA PELAJARAN IPS DI SD - Muh. Kadri Karim (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2019)
ABSTRACTThis study aimed at figuring out the influence of implementing Jeopardy game in learning remedial towards students activities and learning outcomes in Social Science Subject for 5th grade of Elementary School. The subject of this research was the students of 5th grade in Elementary School Mamajang II, second semester and academic year of 2015-2016, who took remedy. This study belonged to experimental research. The research design used was quasi-experimental design which one of its type, nonequivalent control group design, was applied. In case of giving treatment, the experimental class implemented Jeopardy game; on contrary, the lecturing method was used in control class. The data of students learning activities was obtained through observation before treatment section in both experimental and control class. Meanwhile, the learning outcomes were gained through pre-test and post-test in those two classes. The result of research showed that the students activities score before treatment was 57,11 in average for experimental class and 59,38 for control class. Moreover, the averages of students activities score when treatment section were 83,33 for experimental class and 71,46 for control class. Therefore, there were the differences score of students activities between experimental and control class as 11,87. It can be concluded that there was significantincreaseof student activities as 26,22 to the experimental class. On the other hand, the increases of students activities were only 12,08 in control class. In terms of students learning outcomes, it was obtained pre-test score in control class; 45,00 in average and the average post-test score was 70,63. Contrastively, the learning outcomes for experimental class in pre-test were 46,25 in average and the post-test score in average was 86,56. According to the data, there was significant increase of learning outcomes as 40,31 to the experimental class and 25,63 to the control class. The research result was analyzed by using Independent Samples T Test with SPSS for Windows version 21 as program assistance that showed the significant increase of implementing game Jeopardy towards students learning activities and outcomes to the experimental class. According to the research result, it can be concluded that the hypothesis is proved if the implementation of Jeopardy game in remedial learning affects the students activities and learning outcomes in Social Science Subject for 5th grade of Elementary School. Keywords: Remedial learning, Jeopardy game, activities, learning outcomes. ABSTRAKPenelitian ini bertujuan untuk mengetahui pengaruh penerapan game Jeopardy dalam pembelajaran remedial terhadap aktivitas dan hasil belajar mata pelajaran Ilmu Pengetahuan Sosial siswa kelas V SD. Subjek penelitian adalah siswa kelas V di SD Negeri Mamajang II semester II tahun pelajaran 2015-2016 yang mengikuti pembelajaran remedial. Penelitian ini merupakan penelitian eksperimen. Desain penelitian yang digunakan adalah Quasi Experimental Designs dengan menggunakan Nonequivalent Control Group Design. Pada saat perlakuan, kelas eksperimen menerapkan game Jeopardy, sedangkan kelas kontrol menggunakan pembelajaran konvensional (ceramah). Data aktivitas diperoleh melalui pengamatan sebelum perlakuan dan saat perlakuan pada kelas eksperimen dan kelas kontrol. Sedangkan, hasil belajar diperoleh melalui pretest dan posttest pada kelas eksperimen dan kelas kontrol. Hasil penelitian menunjukkan bahwa rata-rata aktivitas siswa sebelum perlakuan pada kelas eksperimen sebesar 57,11 dan kelas kontrol sebesar 59,38. Sedangkan, rata-rata aktivitas siswa saat perlakuan pada kelas eksperimen sebesar 83,33 dan kelas kontrol sebesar 71,46. Sehingga, selisih antara kelas eksperimen dengan kelas kontrol sebesar 11,87. Dapat disimpulkan bahwa terjadi peningkatan aktivitas belajar yang signifikan 26,22 pada kelas eksperimen. Sedangkan, pada kelas kontrol hanya sebesar 12,08. Untuk hasil belajar siswa diperoleh nilai pretest pada kelompok kontrol, yakni rata-rata nilai sebesar 45,00 dan pada posttest rata-rata nilai sebesar 70,63. Sedangkan hasil belajar kelas eksperimen pada saat pretest dengan rata-rata nilai sebesar 46,25 dan pada posttest rata-rata nilai sebesar 86,56. Berdasarkan data tersebut, terjadi peningkatan hasil belajar yang signifikan 40,31 pada kelas eksperimen. Sedangkan, pada kelas kontrol hanya sebesar 25,63. Hasil penelitian dianalisis dengan menggunakan uji Independent Samples T Test berbantuan program SPSS for Windows versi 21 yang menunjukkan bahwa ada pengaruh yang signifikan penerapan game Jeopardy terhadap aktivitas dan hasil belajar siswa pada kelas eksperimen.Berdasarkan hasil penelitian tersebut, maka dapat disimpulkan bahwa hipotesis terbukti bahwa penerapan game Jeopardy dalam pembelajaran remedial berpengaruh terhadap aktivitas dan hasil belajar IPS siswa kelas V SD.  Kata Kunci: Pembelajaran remedial, game Jeopardy, aktivitas, hasil belajar.